Factor influencing enterprise resource planning system: A review - Hasan, Muhammad Syahid; Ebrahim, Zuhriah; Wan Mahmood, Wan Hasrulnizzam; Ab. Rahman, Mohd Nizam (Penerbit UTeM, 2018)
The purpose of this paper is to provide a comprehensive review on factors that influence the enterprise resource planning system (ERP-S) implementation from literature studies between 2011 and 2016.A set of criteria was set to explore ERP-S related research articles through academic search engines and academic databases. Selected articles were categorized into critical success failure factors (CSFF),ERP-S user factors,and ERP-S assimilation factors. The findings from this paper provides a deeper understanding to both academicians and industrial practitioners regarding ERP-S success factors. A strategic plan can also be developed to ensure successful ERP-S implementation.